Kadar kolesterol pada guru yang menjalani Work From Home (WFH) di saat pandemic Covid-19 - Anri Anri; Widyawati Widyawati; Ian Asriani (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Currently, at least one person in every province in Indonesia has tested positive for the Covid-19 virus, so the spread of the virus has become very concerning. All work done from home is referred to as